Out of sight out of mind? A life cycle-based environmental assessment of goods traded by the European Union. (10th February 2020) - Corrado, Sara; Rydberg, Tomas; Oliveira, Felipe; Cerutti, Alessandro; Sala, Serenella
Abstract: Ensuring responsible production and consumption is one of the United Nations' Sustainable Development Goals (SDGs) to which the European Union (EU) has committed. An increasing body of literature has demonstrated that global trade flows are key contributors to the environmental impacts of consumption. Indeed, very often developed countries import fuels and other resources from developing ones, displacing a large share of environmental burdens related to consumption of goods outside their boundaries. This paper has a triple goal. Firstly, it assesses the environmental impacts of traded goods with a bottom-up approach, adopting life cycle assessment (LCA) and identifying hotspots related to EU consumption. Secondly, it analyses the extent to which the trade of goods is contributing to the environmental impacts of EU apparent consumption. Finally, it compares the contribution of environmental impact of EU traded goods against overall global impacts. Forty representative products imported or exported by the EU were selected based on their relevance in mass and economic value according to official trade statistics. LCA was applied to these products using the EU Environmental Footprint method. The results were then upscaled in order to be representative of the entire impact of traded goods in the EU. Overall, consumption in the EU resulted to cause considerable environmental impacts outside EU boundaries and impacts of imports and exports were mostly associated with few products groups, which either were traded in large quantities (e.g. "Fuels and mineral oils") or had a high impact intensity compared to the others (e.g. "Pulp of wood and other cellulosic material" for land use). Graphical abstract: Image 1 Highlights: Method for assessing the environmental impact of traded goods based on Life Cycle Assessment. Relatively few product groups account for a large share of environmental impacts. The environmental impacts of import is higher than export for almost all the impact categories. Environmental impacts of import is dominated by "Fuels and mineral oils". Environmental impact of export is dominated by "Iron and steel", "Machineries", and "Vehicles".